2019
DOI: 10.1177/0300060519865631
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of long-term care quality for older adults in China and Western countries

Abstract: Objective Based on theoretical and methodological research and the results of a literature review, we evaluated and comparatively analyzed the quality of long-term care for older populations in China and in Western countries. Methods We performed a literature review, using the search terms long-term care and care services for older adults, in the databases ProQuest, CNKI, and Wanfang Data. Results Our comparative analysis demonstrated that the overall quantity of articles related to long-term care for older po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 10 publications
(14 reference statements)
0
5
0
Order By: Relevance
“…Countries with a higher level of economic development provide a more favorable proportion of medical and nursing staff for their population 91,92 . However, in some developing countries, multiple issues and limitations relative to developed countries, such as unsound management and security systems, a lack of funds, unreasonable structure of service providers for older people, low quality and level of care, and poor and outdated facilities and equipment, have emerged in the field of social care, 93 which leads patients to rely more on SS. Conversely, without informal SS, stroke patients in developed countries may be able to rely on the care of community medical personnel and national policies and social policy support.…”
Section: Discussionmentioning
confidence: 99%
“…Countries with a higher level of economic development provide a more favorable proportion of medical and nursing staff for their population 91,92 . However, in some developing countries, multiple issues and limitations relative to developed countries, such as unsound management and security systems, a lack of funds, unreasonable structure of service providers for older people, low quality and level of care, and poor and outdated facilities and equipment, have emerged in the field of social care, 93 which leads patients to rely more on SS. Conversely, without informal SS, stroke patients in developed countries may be able to rely on the care of community medical personnel and national policies and social policy support.…”
Section: Discussionmentioning
confidence: 99%
“…Surveys of several Chinese cities have shown that most elderly people have a preference for home and communitybased LTC 5 and the demand is high. 24,25 The reasons were mainly related to the relatively low cost and the sustaining emotional ties.…”
Section: Home and Community-based Ltc For The Elderly In Chinamentioning
confidence: 99%
“…29 The shortage of professionals, low service quality, limited funding channels also hinder its development. 5,15,24 In practice it was found that excessive government intervention in LTC resulted in insufficient supply and caused significant pressure on public finance. As a result, privatisation in LTC services supply emerged to complement public services since 1980s.…”
Section: Home and Community-based Ltc For The Elderly In Chinamentioning
confidence: 99%
See 1 more Smart Citation
“…According to the National Institute on Aging, long-term care includes various services that address individual health and personal needs in two types, formal and informal care. The purpose of LTC is to maintain independence and security of the person [ 4 ]. Informal caregivers are usually family members or friends who care for elderly adults, typically without payment [ 5 ].…”
Section: Introductionmentioning
confidence: 99%